2021
DOI: 10.1101/2021.01.21.427696
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extracellular vesicles regulate yeast growth, biofilm formation, and yeast-to-hypha differentiation inCandida albicans

Abstract: The ability to undergo morphological changes during adaptation to distinct environments is exploited by Candida albicans and has a direct impact on virulence. In this study, we investigated the influence of fungal extracellular vesicles (EVs) during yeast growth, biofilm formation, and morphogenesis in C. albicans. Addition of C. albicans EVs (Ca EVs) to the culture medium positively affected yeast growth. Using crystal violet staining and scanning electron microscopy (SEM), we demonstrated that Ca EVs inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…albicans EVs on invasive hyphae development and virulence, as shown in Galleria mellonella model [31]. Moreover, that study was conducted exploring EVs obtained from yeast cultures, and it is reasonable that the cargo and the message within this EV contribute to cells remain in this form.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…albicans EVs on invasive hyphae development and virulence, as shown in Galleria mellonella model [31]. Moreover, that study was conducted exploring EVs obtained from yeast cultures, and it is reasonable that the cargo and the message within this EV contribute to cells remain in this form.…”
Section: Discussionmentioning
confidence: 99%
“…Many QS molecules might also be found within fungal EVs; however, it is also possible to speculate a cross-regulation between small RNA content in EVs and QS phenomena in fungi. A recent study showed the involvement of QS molecules such as farnesol derivatives and medium-chain fatty acids in EVs obtained from yeast culture as potential regulators of cellular proliferation and yeast-to-hyphae development [31]. The EVs from C. albicans reduced the hyphae and biofilm formation, and the impact of C. albicans EVs on invasive hyphae development and virulence, as shown in Galleria mellonella model [31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations